Specialised features of melanosomes in health and disease in the retinal pigment epithelium - Doncheva, Dilyana; Eden, Emily R.; Futter, Clare E. (Frontiers in Cell and Developmental Biology, 2025)
This mini-review focuses on melanosome biogenesis, positioning and function in the retinal pigment epithelium (RPE) where melanosomes absorb light scatter and protect against the harmful effects of photo-oxidation. RPE melanosomes share a common biogenesis pathway with those of skin melanocytes but are made primarily embryonically and are retained by the RPE throughout life. They do however move from the cell body into the apical processes which, in mammalian RPE, is regulated by a machinery related to that regulating melanosome distribution in skin melanocytes. Melanosomes in the RPE make extensive membrane contacts with the ER and mitochondria although their role in adult RPE remains to be fully established. Albinism is associated with multiple visual defects and reduced or absent pigmentation in melanosomes has implications for long term visual health. Age-related changes in melanosomes have been implicated in retinal degenerative disease, including age-related macular disease (AMD). The lysosomes of the RPE have an unparalleled degradative burden arising from the daily phagocytosis of the distal tips of photoreceptor outer segments, which is part of a daily process of outer segment renewal. A failure to fully process the phagocytosed outer segments leads to a build-up of the toxic ageing pigment, lipofuscin, which accumulates in all ageing RPE. Melanolipofuscin also accumulates in the RPE with age and may result from melanin-mediated degradation of lipofuscin through melanin chemiexcitation. Age-related loss of melanosome-mediated protection could be an important component of age-related visual decline.